Pembelajaran Berbasis Masalah untuk Mengembangkan Kemampuan Literasi Statistika Siswa di Sekolah Dasar - Wulandari, Tri Mitalia Endah; Hidayah, Refiana; Faatin, Nisriina Amiirah; Murtiyasa, Budi; Setyaningsih, Nining (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the application of the Problem-Based Learning (PBL) model in developing elementary school students' statistical literacy skills. This study used a descriptive qualitative approach involving 16 sixth-grade students from Sanggrahan Public Elementary School in Surakarta City. Data were obtained through observation, interviews, and document analysis, then analyzed using the Miles & Huberman model. The results showed that the application of PBL was able to improve students' data interpretation skills, critical thinking, and active involvement in statistics learning. Students admitted that it was easier to understand the material because the learning activities involved real experiences and group discussions, while teachers and the principal stated that PBL had a positive impact on the quality of learning even though it required more preparation and time. Factors supporting success included teachers' mastery of PBL, adequate facilities and infrastructure, and school support; while obstacles included time constraints and the need for intensive preparation. This study confirms that PBL is an effective approach to improve elementary school students' statistical literacy and is relevant for application in contextual mathematics learning. Keyword: Problem-Based Learning, Statistical Literacy, Elementary School.